2020
DOI: 10.1021/acs.est.0c01231
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Tannic Acid-Fluoride Inhibition of Ammonia Emissions and Simultaneous Reduction of Methane and Odor Emissions from Livestock Waste

Abstract: Gaseous emissions from livestock production are complex mixtures including ammonia, methane, volatile organic compounds (VOC) and H 2 S. These contribute to eutrophication, reduced air quality, global warming and odor nuisance. It is imperative that these gases are mitigated in an environmentally sustainable manner. We present the discovery of a microbial inhibitor combo consisting of tannic acid and sodium fluoride (TA-NaF), which exhibits clear synergistic inhibition of ammonia production in pure bacteria cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 78 publications
2
18
0
1
Order By: Relevance
“…Cumulative methane emission was slightly lower in TA-NaF treated manure than in untreated manure, but the reduction was not statistically significant. This is in agreement with Dalby et al [ 17 ], where no difference was found in methane production during the first 14 days of incubation with 2.5:1 mM TA:NaF. Carbon dioxide production in TA-NaF treated swine manure was not significantly different from untreated swine manure either ( Fig 3B ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Cumulative methane emission was slightly lower in TA-NaF treated manure than in untreated manure, but the reduction was not statistically significant. This is in agreement with Dalby et al [ 17 ], where no difference was found in methane production during the first 14 days of incubation with 2.5:1 mM TA:NaF. Carbon dioxide production in TA-NaF treated swine manure was not significantly different from untreated swine manure either ( Fig 3B ).…”
Section: Resultssupporting
confidence: 93%
“…The detrimental effects of methane, reduced sulfur compounds and several other livestock gases on the climate and environment have raised the demand for innovating sustainable mitigation technologies. In recent studies, methane and reduced sulfur compounds emissions were significantly reduced from swine manure using tannic acid with sodium fluoride (TA-NaF) as inhibiting agent [ 17 ]. It was shown that inhibition with TA-NaF was of synergistic nature and it was proposed that the mode of inhibition was related to TA disrupting the cell membrane, which allows toxic fluoride to flow into the cell and inhibit metabolism [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the available literature regarding NH3 as an odor indicator, some mixed results were found. Some studies indicated NH3 as a poor indicator of odor emission [19][20][21][22], whereas contemporary studies reported the inhibition of NH3 emission with simultaneous odor reduction [23][24][25]. In general, NH3 concentration in swine barn is proportional to the amount of protein and amino acids decomposed, and so is the odor emission [26,27].…”
Section: Introductionmentioning
confidence: 99%